Antischistosomal tetrahydro-γ-carboline sulfonamides. (1st March 2022) - Ren, Rongguo; Wang, Xiaofang; Leas, Derek A.; Häberli, Cécile; Cal, Monica; Dong, Yuxiang; Kaiser, Marcel; Keiser, Jennifer; Vennerstrom, Jonathan L.
Graphical abstract: Abstract: We discovered tetrahydro-γ-carboline sulfonamides as a new antischistosomal chemotype. The aryl sulfonamide and tetrahydro-γ-carboline substructures were required for high antischistosomal activity. Increasing polarity improved solubility and metabolic stability but decreased antischistosomal activity. We identified two compounds with IC50 values <5 µM against ex vivo Schistosoma mansoni .